Managing knowledge and information resources in Private Islamic University Library - Abu Bakar, Qudri Ali; Mat Yatin, Saiful Farik; Kamarulzaman, Mohd Sharulnizam; Toha @Tohara, Abdul Jalil; Hashim, Khairusy Syakirin Has-Yun; Wan Mohd Saman, Wan Satirah; Khairuddin, Irni Eliana; Nik Ariffin, Nik Azliza (Human Resource Management Academic Research Society (HRMARS), 2020)
This article discusses on the finding of how Private University Islamic Library take control in managing its knowledge and information as source in the university in extent with their capabilities of their daily operations in utilizing top-notch resources available in order to support educational functionality as it pars with their core businesses institutions. The services offered, space design and layout, technology and application that implies accordance to the main subject of this case study at this Private University Islamic library. The services offered were commonly and conventionally been introduced by most academic library in the world and some of the technologies utilized in this library were obsolete due to few factors that has been contributed to the findings. The intention of this paper written is also to discuss about the recommendation for improvement on their services as well as other features based on the problems listed. This library should take necessary interventions in order to upgrade the current quality services with the outlined alternatives.